Digital Forensics and Cyber Crime : 7th International Conference, ICDF2C 2015, Seoul, South Korea, October 6-8, 2015. Revised Selected Papers - James, Joshua I.; Breitinger, Frank; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the 7th International Conference on Digital Forensics and Cyber Crime, ICDF2C 2015, held in Seoul, South Korea, in October 2015. The 14 papers and 3 abstracts were selected from 40 submissions and cover diverse topics ranging from tactics of cyber crime investigations to digital forensic education, network forensics, and international cooperation in digital investigations.
Digital Forensics Education -- Computational Forensics -- Network and Cloud Forensics -- Cooperation in Digital Investigations -- Social Media Investigations -- Computer and Device Forensics.
Keywords: Computer security; Computers -- Law and legislation; Computer science; Information Systems; Systems and Data Security; Legal Aspects of Computing; e-Commerce/e-business.; Computers and Society; Management of Computing and Information Systems